Factors Affecting the Presence of Renal Cortical Cysts in Kidney Donors - Sevim Nuran Kuşlu Çiçek; Amil Huseynov (Urology Research and Practice)
Objective: Simple renal cysts (SRCs) represent the most frequently occurring type of renal cysts, frequently observed in the elderly population. While generally considered benign, SRCs may sometimes be connected to comorbid conditions such as hypertension, aortic diseases, and renal dysfunction. This research aims to investigate the factors influencing the development of SRCs in kidney donors and the associated risks.